Teologiczne znaczenie „monarchii” a pojęcie Boga w "De Trinitate" Nowacjana - Sordyl, Krzysztof (Vox Patrum, 2009)
The Novatian’s tractate does not use the term, instead, the person of Sabellius takes a prominent place. Hence, in order to better understand Novatian himself, the present study demonstrates how the term was used by such authors as Tertullian, Hippolytus, or the author of the Refutatio. An attempt has also been made to establish the place that monarchy took in Patripassian theology. Novatian does not mention monarchy because his polemic against Patripassianism is in reality a confrontation with Sabellianism, as it was known in Rome in the first half of the third century. Novatian directly opposes Sabellius who, at least during his Roman period, did not use the concept to defend and substantiate his heresy. Patripassianism, such as Novatian came to know in Rome, was indeed Sabellianism. The Roman theologian refers to ideas contained in the term when he defends monotheism (against Gnostics and Marcion) and refutes the charges of ditheism from Patripassians. The author of De Trinitate continues his polemic against Gnostic and Marcionite dualism, when he acts in defense of monotheism and the creative act of God. He refers to the content of the term to rule out the existence of a god superior to the Creator. Divine agenesia guaranties, according to Novatian, that there is no god superior to God the Creator. The Roman author engages in a polemic with the Marcionite concept (the distinction between good and just God). He presents interrelationship between the goodness of God and creation. Evil originates in the free will of man, and is not connected with matter or attributed to God in His creative act. In order to refute Gnostic dualism, Novatian refers to the content of monarchy. In the same way he substantiates the immutability of God. In his view, the fundamental source of God’s immutability is His agenesia. Refuting the concept of eternal matter, not created by and independent from God, the Roman theologian once again uses the content of the term. In De Trinitate Novatian continues the line of thinking of these authors who developed the concept of monarchy. Novatian quotes Rom 11:36, which text is usually interpreted in the Trinitarian sense. The Roman author uses it to write about creative mediation of the Word. The Roman theologian also quotes biblical evidence for the divinity of Christ in his polemic with Adoptianists and Patripassians: Jn 1:1 (the key text of the theology of the Logos); Jn 1:14 (most frequently quoted text in De Trinitate) and Rom 9:5. Novatian points out that Scripture does not contradict itself, presenting both unity and diversity between the Divine persons.